제4차 산업혁명에 대응하는 인공지능(AI)에 의한 지식재산 시스템에 관한 고찰 - 김남진(Namjin Kim); 김옥근(Okgeun Kim); 문사성(Saseong Moon); 조재신(Jaeshin Jo) (디지털콘텐츠학회논문지, 2019)
4차 산업혁명을 맞아 수많은 분야에서 인공지능(Artificial Intelligence, AI) 창작물들이 등장하고 있으며, AI의 창작물이 누구의 소유인지, 인공지능이 창작할 때까지 사용한 디지털 데이터들의 권리는 어떻게 보상할 것인지 등 다양한 논의가 되고 있다. AI 프로그램이 점점 정교해지고 발달함에 따라 타인의 지식재산권을 침해할 가능성이 커지고 있다. 본 논문에서는 권리침해 시 보다 쉬운 분쟁해결 방법을 위하여 Tracing 방법을 통해 인공지능이 기술 발명, 또는 창작물을 만들 때 사용되었던 디지털 데이터들의 경로 및 출처를 확인하여 추후 발생할 수 있는 지식재산권 침해 분쟁들을 보다 쉽게 해결할 수 있는 방안을 제시한다. With the fourth industrial revolution, AI (Artificial Intelligence) creations are appearing in many fields, and various discussions are being held, including whose creation AI is owned and how to compensate for the rights of digital data used in the creation of artificial intelligence. As AI programs become more sophisticated and developed, there is a growing possibility that they will infringe on other people's intellectual property rights. In this paper, the "Tracing" method identifies the path and source of digital data used to create technology inventions or creations in order to make conflict resolution easier in the event of infringement of rights, so as to make it easier for artificial intelligence to resolve potential intellectual property infringement disputes. KCI Citation Count: 2